FPGA-based digital controller for dc-dc converter - Abd. Rahman, Diyya Hidayah (2014)
This thesis presents a FPGA-based digital controller for a DC-DC converter. The converter topologies chosen in this project is Non-Inverting Buck-Boost converter. The main difference from DSP-based solution is that FPGA allows simultaneous execution of all control procedures. The control algorithm has been developed using Verilog language based on the voltage control loop. The FPGA switching controller has been designed as simple as possible while maintaining the accuracy and dynamic response. The DE1 board is used to control the main circuit. Simulations and experimental results show the feasibility of the proposed method, opening interesting possibilities in motion and power electronics converter control.